Development of Multimedia-Based Learning Media for Multimedia Courses - Sumual, Shelty D M; Lumapow, Harol R; Tuerah, Philotheus E A; Dondokambey, Clay J H; Paat, Wensi R L; Manumpil, Yulit B (International Journal of Information Technology and Education, 2024)
This research is research into the development of learning media which aims to produce learning media for Multimedia courses which is expected to help lecturers in the teaching and learning process. This research is research into developing the Multimedia Development Life Cycle (MDLC). In this method there are 6 (six) stages, namely: (1) Concept, (2) Design, (3) Obtaining Content Material, (4) Assembly, (5), Testing, (6) Distribution. In this testing phase, there are four testing forms: Developer Tests, Media Experts, Material Experts, and End -End-user tests. The research obtained good results, and from these results, the research concluded that the application of multimedia learning media.